VATIS update : food processing. Vol. 3, No. 75, Jan-Feb 2006 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2006)
Highlights - Test for avian flu virus in foods - “Salty” salt replacer - Capsulized protein beverage - Fighting fresh fruit decay - The world’s first clear aseptic package - Cold milk skimming system IN THE NEWS …4 Organic consumption higher than average in Asia-Pacific✓ Imported milk products rule Vietnamese market ✓Korea to set up new food hygiene task force ✓Chinese market sees biscuit boom ✓ Food equity fund planned in India ✓Pakistan to boost FDI in retail and food sectors ✓ Shrimp tracked from farm to table ✓Palm oil ‘reasonable’ replacement for trans-fats QUALITY CONTROL …7 Cold plasma devices to kill food pathogens ✓Rapid measurement of egg quality ✓ Spectrometer helps processors to the right blend ✓ Test for avian flu virus in foods ✓ Analysis of fat and dry matter in cheese ✓New system sets standard for bread quality control INGREDIENTS …9 New emulsifier promises viscosity and better yield ✓Water-resistant edible film from milk ✓Making dark chocolate and ice cream compatible ✓ New ingredient could support grain claim to protein bars ✓New fruit ingredient for texture retention ✓ Taste-neutral flavour enhancing yeast extract ✓ “Salty” salt replacer STANDARDS/REGULATIONS …11 Indian food law under Parliament Committee’s scrutiny ✓ Malaysia tells palm oil players to convert to new licence ✓Philippines strengthens implementation of Food Fortification Act BEVERAGES …12 Nestle develops foaming coffee beer system ✓The first authentic aromatherapy drink ✓Capsulized protein beveragee ✓Low-GI beverage solution PRESERVATION …13 Fighting fresh fruit decay ✓Meat’s shelf-life stretched to months ✓ New technology for cold pasteurization ✓ Fresh idea aids shelf-life of fruit PACKAGING …14 Desiccant additive extends packaging shelf-life ✓ High-speed packaging machine ✓Multi-function horizontal packer ✓Robots help automate biscuits packaging ✓The world’s first clear aseptic package ✓High- performance vacuum packaging systems ✓Gas packaging extends cheese shelf-life MACHINERY/EQUIPMENT …16 Cold milk skimming system ✓ ...